PENGARUH LEVERAGE, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2010-2012 - Ngadiman, Ngadiman; Puspitasari, Christiany (Jurnal Akuntansi, 2014)
The purpose of this study is to obtain empirical evidence about the effects ofleverage, institutional ownership,and firm size on tax avoidance of the manufacturing companies listed on the Indonesian Stock Exchange from 2010-2012. Tax avoidance is a dependent variable, while leverage, institutional ownership, and firm size are independent variables. The data used are secondary data and sample of 170 financial statements of listed companies on the Indonesian Stock Exchange from 2010-2012. This research used non-random sampling. The sampling used purposive sampling and the data were analyzed by using multiple linear regression analysis. Data were analyzed using SPSS software 21 version. The result of the research showed that leverage has no significant effects on tax avoidance, while institutional ownership and firm risk have significant effects on tax avoidance. To get better research results, further researches may add other variables that have major impact probabilities, use companies other than manufacturing, and extend the period of study.